Sosialisasi Penggunaan Akun Google Sebagai Media Pembelajaran Digital Bagi Guru SD Negeri 060856 Medan - Mufida Khairani; Divi Handoko; Boni Oktaviana Sembiring; Arie Rafika Dewi; Yulia Agustina Dalimunthe (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The development of technology today has been widely used by humans. Not only in industry and companies, but has penetrated the world of education, where the use of computer devices and applications is used by teachers and students. In the use of an online-based computer, a google account is needed that can be used to access email and other google media applications such as google classroom, google meet, google drive, google doc, google slides, google calendar, google form and so on. This training was conducted at SD Negeri 060856 Medan by utilizing a Google account as a digital-based learning medium. This training aims to increase teachers' knowledge and insight in making interesting learning and increase the effectiveness of digitalization-based learning. As a result of this activity, teachers can understand the use of media tools such as gmail, google classroom and google meet.